A New Paradigm in Parent-School Relationships - Robert McKinney, Jr (The University of Alabama, 2022)
Review of the book: Soo Hong, A Cord of Three Strands: A New Approach to Parent Engagement in Schools. Cambridge, MA: Harvard Education Press, 2011. ISBN 978-1934742549